Performance and sustainability of self-compacting mortars made with recycled aggregate and supplementary cementitious materials - Ulucan, Muhammed; Cebeci, Ibrahim (Elsevier, 2025)
This research focuses on the utilization of construction and demolition waste generated after destructive earthquakes and presenting a sustainable design for self-compacting mortar and concrete technology, which is widely used in newly constructed buildings. A comprehensive laboratory study is presented, and engineering, environmental and economic properties of 10 different mortar series were investigated. In all designs, recycled aggregates and supplementary cementitious materials (SCM) were used. The MK15 series achieved satisfactory results in terms of final age compressive strength (180 days), showing an increase of approximately 29.0-6.9 % in compressive and flexural strengths, respectively. In high-temperature tests conducted at 600 and 900 degrees C, compressive strength decreased by approximately 35-65 %, and flexural strength decreased by approximately 45-75 %. For sulfate resistance tests, the lowest decrease in compressive strength was observed in the MK15 (9.2 %), while the lowest decrease in flexural strength was seen in the MK10-FA (9.9 %). Evaluation of microstructural properties also revealed that SCM significantly contributes to gel formation and improves microstructural properties. Similarly, satisfactory results were obtained for the seven impact categories considered in the environmental impact assessment. Review of life cycle assessments and economic outputs demonstrated the critical importance of cement and the effectiveness of the design considered. Therefore, this research represents a sustainable approach by reducing cement consumption for self-compacting concrete and mortar technology, which is widely used in new buildings, by enabling the utilization of waste materials generated in countries located in active earthquake zones and subjected to devastating earthquakes (7.7-7.6-6.8-6.6 Mw) in recent years, such as Turkey.
Keywords: Sustainable design; Low-carbon cement; Life cycle assessment; Recycled aggregate